Bahasa inggris - Camilia Habibah; Wati Sukmawati (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the effect of Project-Based Learning (PjBL) integrated with STEAM on the creative thinking skills of fifth-grade elementary school students regarding the human respiratory system. The study employed a quantitative approach using a quasi-experimental pretest-posttest control group design. The sample consisted of 46 students divided into an experimental class (n = 21) and a control class (n = 25) at a public elementary school in West Jakarta. The research instrument was a creative thinking ability test comprising 20 items, analyzed using the Rasch model via the Winsteps 4.8.2 application. The analysis results showed an improvement in ability in both classes following the intervention. The control class improved from 1.51 logits on the pretest to 2.48 logits on the posttest, with a gain of 0.97 logits. Meanwhile, the experimental class showed a greater increase, rising from 2.48 logits to 4.82 logits, with a gain of 2.34 logits. The Rasch analysis results also showed that all test items had a good level of fit with the model (infit and outfit MNSQ values were in the range of 0.5–1.5), so the data were deemed valid and suitable for use. Based on these results, it can be concluded that PjBL-based STEAM learning is more effective in improving students’ creative thinking skills than conventional learning when teaching the human respiratory system.